2012
DOI: 10.2139/ssrn.2112029
|View full text |Cite
|
Sign up to set email alerts
|

Policy, Technology, and Efficiency of Brazilian Agriculture

Abstract: The U.S. Department of Agriculture (USDA) prohibits discrimination in all its programs and activities on the basis of race, color, national origin, age, disability, and, where applicable, sex, marital status, familial status, parental status, religion, sexual orientation, genetic information, political beliefs, reprisal, or because all or a part of an individual's income is derived from any public assistance program. (Not all prohibited bases apply to all programs.) Persons with disabilities who require altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 19 publications
(16 reference statements)
0
25
1
5
Order By: Relevance
“…Over three-quarters of the investment credit disbursed between 1985 and 2006 has been issued to the livestock sector, boosting livestock's credit investments by 4.7% annually, more than double the investment credit allocations for crops during the same period. The livestock sector's greater growth in investment credit indicates Brazil's priority of modernizing livestock production [48].…”
Section: Brazilmentioning
confidence: 99%
See 3 more Smart Citations
“…Over three-quarters of the investment credit disbursed between 1985 and 2006 has been issued to the livestock sector, boosting livestock's credit investments by 4.7% annually, more than double the investment credit allocations for crops during the same period. The livestock sector's greater growth in investment credit indicates Brazil's priority of modernizing livestock production [48].…”
Section: Brazilmentioning
confidence: 99%
“…Rural credit is provided by credit cooperatives and by the commercial banks, participants in the National Rural Credit System (NRCS). NRCS was created in 1965 to quicken capital formation in exportable farm products [48]. The rules and conditions to be observed regarding loans are established by the National Monetary Council (NMC), which is a body connected to the Finance Ministry and the application of these rules and conditions is examined by the Central Bank [49].…”
Section: Brazilmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, Huang et al (2011), analysing the impact of China's agricultural subsidies, found that input subsidies appear to be non-distorting in terms of producer decisions. Rada and Valdes (2012) showed that the benefi ts of agricultural research have been most rapidly adopted by the most effi cient farms, while other public policies including rural credit and infrastructure investments, favoured 'average' producers. Minviel and Latruff e (2014) found that targeted investment subsidies were positively associated with farm's technical effi ciency, while Bojnec and Latruff e (2013) found that agricultural subsidies reduced the technical effi ciency of Slovenian farms but improved their profi tability.…”
Section: Introductionmentioning
confidence: 99%